GAMBARAN KUALITAS HIDUP PASIEN KANKER DI MASA PANDEMI - Harahap, Romaito Arohman; Deli, Hellena; Agrina, Agrina (Coping: Community of Publishing in Nursing; Vol 10 No 2 (2022): April 2022DO - 10.24843/coping.2022.v10.i02.p09, 2022)
The quality of life can affect the physiology and psychology of cancer patients. Adaptation of medical care during the pandemic can cause anxiety, depression, and worry about being infected with Covid-19. This study aims to describe the quality of life of cancer patients during the pandemic at Arifin Achmad Hospital. This research method is descriptive design with purposive sampling technique. The research sample was 60 respondents. The researcher used EORTC QLQ-C30 questionnaire as the instrument to assess the quality of life patient with cancer and used univariate analysis to describe the quality of life of cancer patients. The result of this study showed that majority of respondents were female (81,7%), majority age range was 46-55 years (43,3%), majority respondents wasn’t work again (78,3%), respondents with breast cancer (61,7%), stage III cancer (48,3%), duration of diagnosis >1 year (68,3%) and the majority of chemotherapy treatment (63,3%). Quality of life in cancer patients, it was found that 96,7% had moderate quality of life. The results showed that the number of cancer patients with good quality of life based on physical function (73,3%), role function (71,7%), emotional function (83,3%), cognitive function (91,7%), social function (83,3%). Meanwhile, on the symptom scale, 45 people (75%) had poor quality of life and 38 people (63,3%) had good quality of life on the general health scale.